Improved Open‐ Circuit Voltage in ZnO–PbSe Quantum Dot Solar Cells by Understanding and Reducing Losses Arising from the ZnO Conduction Band Tail. Issue 8 (21st February 2014) - Hoye, Robert L. Z.; Ehrler, Bruno; Böhm, Marcus L.; Muñoz‐Rojas, David; Altamimi, Rashid M.; Alyamani, Ahmed Y.; Vaynzof, Yana; Sadhanala, Aditya; Ercolano, Giorgio; Greenham, Neil C.; Friend, Richard H.; MacManus‐Driscoll, Judith L.; et al.
<x xml:space="preserve">Abstract</x> Colloidal quantum dot solar cells (CQDSCs) are attracting growing attention owing to significant improvements in efficiency. However, even the best depleted‐heterojunction CQDSCs currently display open‐circuit voltages (VOCs) at least 0.5 V below the voltage corresponding to the bandgap. We find that the tail of states in the conduction band of the metal oxide layer can limit the achievable device efficiency. By continuously tuning the zinc oxide conduction band position via magnesium doping, we probe this critical loss pathway in ZnO–PbSe CQDSCs and optimize the energetic position of the tail of states, thereby increasing both the VOC (from 408 mV to 608 mV) and the device efficiency.